REACTUALIZATION OF ISLAMIC LAW FROM THE PERSPECTIVE OF MUNAWIR SJADZALI - Bakti Prasetyo; Fadil SJ (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The reactualization of Islamic law has been a topic of interest for scholars and scholars across the world. This research aims to analyze the implications of Munawir Sjadzali's perspectives on Islamic law in contemporary Indonesian society. The research employed a library research approach, focusing on qualitative descriptive analysis. The analysis was conducted through a process of thematic analysis, identifying and interpreting patterns related to the adaptation and reinterpretation of Islamic teachings. Deductive and inductive reasoning were applied to draw conclusions from the literature, facilitating a deeper understanding of the implications. The study provides a nuanced view of how Islamic law can be relevant and applicable to modern societal challenges, potentially influencing both academic thought and practical applications within Islamic jurisprudence. It may offer guidance for policymakers and legal practitioners in integrating traditional Islamic principles with contemporary legal frameworks.